NOTA SOBRE UNA PENTOSA ECONTRADA EN EL MUSCULO CARDIACO - VELEZ OROZCO, J; SODI PALLARES, ERNESTO; RIVERO CARVALLO, J (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1948)
Direct auricular electrograms show only slight asynchronism, depending on the distance from the pacemaker However, when the electrodes were systematically placed around the periphery of the obstacle constituted by the orifices of the venae cavae, plus an
ARCH INST CARDIOL MEX
Keywords: NOTA, PENTOSA, MUSCULO, CARDIACO; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA